Transformasi Bisnis Digital dalam Mendukung Keberlanjutan Lingkungan - Zulhamdani; Hafizah Rifiyanti (JURNAL TECNOSCIENZA, 2026)
The increasing industrial activities and rapid development of digital technology have significantly impacted the environment, including rising energy consumption, carbon emissions, and the exploitation of natural resources. These conditions highlight the need for more effective, efficient, and sustainable environmental management strategies through the utilization of digital technologies. Digital business transformation has emerged as one of the approaches considered capable of supporting environmental sustainability through the integration of information technology in resource management and environmental monitoring. This study aims to analyze the role of digital business transformation in supporting environmental sustainability through the utilization of digital technologies in resource management and environmental monitoring. The research method used is a literature review with a descriptive qualitative approach, examining various scientific articles and previous studies related to digital transformation, information technology, and sustainable environmental management. The results indicate that the implementation of digital technologies such as the Internet of Things (IoT), big data, artificial intelligence, and cloud computing can improve operational efficiency, enhance the accuracy of real-time environmental monitoring, and support data-driven decision-making within organizations. In addition, digital business transformation contributes to improving environmental performance, increasing transparency in resource management, and reducing negative impacts on the environment. Therefore, digital business transformation has become an important strategy in achieving more effective, efficient, and sustainable environmental management.